2014
DOI: 10.1007/s10935-014-0376-x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting in 2 Worlds: Pilot Results From a Culturally Adapted Parenting Program for Urban American Indians

Abstract: This study reports the implementation and feasibility of a culturally adapted parenting curriculum, Parenting in 2 Worlds (P2W), which we designed specifically for urban American Indian families by means of community-based participatory research and then pilot tested in three Arizona cities. Data come from matched pre- and post-test surveys completed in 2012 by 75 American Indian parents of adolescents aged 10–17 who participated in the pilot version of P2W. P2W is a 10-workshop program administered twice a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Adaptation decisions in the second iteration were driven by working with communities to identify core components to add, change, or adapt. This iteration of BZDDD can be classified as a deep-structure cultural adaptation (Okamoto et al, 2014b), like that of the Parenting in 2 worlds adaptation (Kulis, Ayers, & Baker, 2015) reflecting a method to infuse cultural views, beliefs, and values, into the curriculum.…”
Section: Case Study 1 - Bii-zin-da-de-dahmentioning
confidence: 99%
“…Adaptation decisions in the second iteration were driven by working with communities to identify core components to add, change, or adapt. This iteration of BZDDD can be classified as a deep-structure cultural adaptation (Okamoto et al, 2014b), like that of the Parenting in 2 worlds adaptation (Kulis, Ayers, & Baker, 2015) reflecting a method to infuse cultural views, beliefs, and values, into the curriculum.…”
Section: Case Study 1 - Bii-zin-da-de-dahmentioning
confidence: 99%
“…In the second adaptation phase, the pilot version of P2W was delivered to 75 AI participants at three sites in different Arizona cities. The pilot test demonstrated that there were statistically significant improvements in parenting outcomes from pretests to post-tests, using the same measures examined in the current study (Kulis et al, 2015). …”
Section: Parenting In 2 Worldsmentioning
confidence: 53%
“…This analysis examines six widely used measures of parenting skills and family functioning that were primary targets of the intervention; the acceptable psychometric properties of these measures were verified in the study’s pilot phase (Kulis, et al, 2015). Each outcome was constructed as a mean scale from Likert-type responses to multiple items (reversing the valence as needed), with good to excellent reliability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations